The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.neuroimage.2017.12.069
|View full text |Cite
|
Sign up to set email alerts
|

More highly myelinated white matter tracts are associated with faster processing speed in healthy adults

Abstract: The objective of this study was to investigate whether the estimated myelin content of white matter tracts is predictive of cognitive processing speed and whether such associations are modulated by age. Associations between estimated myelin content and processing speed were assessed in 570 community-living individuals (277 middle-age, 293 older-age). Myelin content was estimated in-vivo using the mean T1w/T2w magnetic resonance ratio, in six white matter tracts (anterior corona radiata, superior corona radiata… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Several studies have reported that the corona radiata is stiffer than the corpus callosum (Budday et al, 2017;Johnson et al, 2013), which agrees with our measurements of 3.36 ± 0.33 kPa and 3.05 ± 0.32 kPa, respectively. There is evidence to suggest that the corona radiata possesses more myelin than the corpus callosum (Chopra et al, 2018), and thus myelin content could contribute to the higher stiffness reported (Weickenmeier et al, 2016(Weickenmeier et al, , 2017. Notably, the fornix, which is part of the limbic system and is critically involved in the formation of new memories (Douet & Chang, 2015;Schwarb et al, 2019), is particularly soft and exhibits greatest variability among participants for both MRE measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the corona radiata is stiffer than the corpus callosum (Budday et al, 2017;Johnson et al, 2013), which agrees with our measurements of 3.36 ± 0.33 kPa and 3.05 ± 0.32 kPa, respectively. There is evidence to suggest that the corona radiata possesses more myelin than the corpus callosum (Chopra et al, 2018), and thus myelin content could contribute to the higher stiffness reported (Weickenmeier et al, 2016(Weickenmeier et al, , 2017. Notably, the fornix, which is part of the limbic system and is critically involved in the formation of new memories (Douet & Chang, 2015;Schwarb et al, 2019), is particularly soft and exhibits greatest variability among participants for both MRE measures.…”
Section: Discussionmentioning
confidence: 99%
“…Neurite orientation dispersion and density imaging (NODDI) 18 may offer more sensitivity and specificity as it models changes in fiber dispersion (orientation dispersion index [ODI]) as well as density of the tissue microstructure (intracellular volume fraction [ICVF]). NODDI has been successfully applied in studies of typical development 19 , 20 and clinical populations 21 but not yet in SCA.…”
mentioning
confidence: 99%
“…Given the effects of exercise on executive functions and processing speed (Colcombe & Kramer, 2003;Kramer & Colcombe, 2018) and the reliance of processing speed on WM integrity (Chopra et al, 2018), we were surprised to find no associations between change in T1w/T2w and change in these two cognitive domains. Although we observed performance decline trends in the control group for the executive function and processing speed components, these were not statistically significant.…”
Section: Episodic Memory and T1w/t2wmentioning
confidence: 80%